Comparing Central Europe and the Baltic macro-economies: A Bayesian approach - Elton Beqiraj; Giovanni Di Bartolomeo; Marco Di Pietro; Carolina Serpieri (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2018)
Applying the Bayesian approach, a small open economy DSGE model was estimated using a sample of quarterly data for a macro-region formed by six Central Europe and Baltic economies: Czech Republic, Estonia, Hungary, Lithuania, Poland, and Slovakia. Estimates have been employed to investigate the effects of a financial crisis, exploring the role played by country differences in the relative performances. We also use our Bayesian estimations to compute two measures of resilience in the considered region.
Keywords: E02; E32; E58; 330; resilience; Bayesian estimations; financial crisis; macroeconomic performance; emerging markets